Gerenciamento do abastecimento de mercadorias utilizadando a reposi????o autom??tica de estoques - Ihy, Mauro Takeo (2006)
Since the 1990???s there has been an increase in general competition in the Brazilian scenario and a great evolution in the technological area has occurred, leading to significant changes in companies. Allied with increasing competition and the presence of a more demanding consumer, who prizes good attention and quality service , logistics has played a fundamental role in business management, which has enabled the development of strategies that focus on the efficiency of supply chains as a whole. In this context, retail and wholesale companies have sought means of improving their logistic processes, with the purpose of meeting the needs of their consumer market in an efficient way. As far as supply management is concerned, VMI ??? Vendor Managed Inventory and RMI ??? Retail Managed Inventory provide an important alternative to managed processes and inventory management. These techniques allow wholesalers and retailers to have suitable inventories in terms of quantity and precise arrival time. This dissertation aims at describing, detailing and evaluating the supply management of a wholesale chain regarding the strategic contribution of logistic processes, particularly the automated inventory system. Accordingly, an empirical-theoretical approach has been adopted for only one case study in order to enable its thorough comprehension. The current study was based on a Dutch wholesale chain, Makro, which has been in Brazil since 1972, and currently comprises 52 stores. The study offers details regarding the company evolution and more specific information on commercial activities, ways of supply management, inventory control, ECR tools (Efficient Consumer Response). Furthermore, it highlights the operation of the automated inventory process. It is believed that this study offers important details as to the way the supply processes of the studied company are conducted as well as it shows the importance of the automated inventory system in business results.